A Study to Measure Prevalence of Goiter in School Children of Narmada District, Gujarat - Jyotsna M Pandor; Jivraj R Damor; Navneet G Padhiyar; Govind L Ninama (Medsci Publications, 2011)
Introduction: - Iodine is essential micronutrient with an average daily requirement of 100-150 micrograms for normal human growth and mental development. Inadequate or poor intake of iodine can result in physical and mental retardation. It affects people of all ages, both sexes and of different socio economic backgrounds. The disorders caused due to deficiency of nutritional iodine in the food /diet are called Iodine Deficiency Disorders (IDD) Aim: To find out the prevalence of goiter in school children and in the Community children aged between 6-12 years. Study design: - A sample of 30 villages/wards has to be selected from the district. The method of sampling to be used is PPS systematic sampling. Results: - Total prevalence of goiter was found 18.1% in the Narmada district with 12.4% of grade 1 and 5.7%   of grade 2. Nodule was found in only 5 children.